Diagnóstico Financiero y Estratégico de la Empresa Royal DSM para los periodos 2014 -2016 - Barrantes-Echandi, Diego; Calderón-Miranda, Giovanni; Quirós-Voto Bernales, Alonso (Instituto Tecnológico de Costa Rica, 2017)
Royal DSM is Holland based global company with operations in all 5 continents. It mission is to create brighter lives for people today and generations to come through active science in the fields of health, nutrition and supplies. During the period 2010-2015, the company focused on a strategy of growth called “Driving Focused Growth” on which market mega—trends were identified, as well as how to reach them (Health and Well-Being, Global Changes and Climate, and Energy). Part of this strategy consisted of the acquisitions of other companies. Since 2016, and a final term up to 2018, Royal DSM starts a new strategy called “Driving Profitable Growth” which is pretended to profit on the management applied during the period 2010-2015 with. This current project seeks to determine of financial effects aligned the objectives expected from both strategies. This will be achieved through the elaboration of a financial diagnosis on which main tools available were used through an automated spreadsheet that can be applied in the future to make financial diagnosis for any other company.
Proyecto de Graduación (Maestría en Administración de Empresas) Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, 2017.
Keywords: Diagnóstico financiero; Estrategia; Indicadores; EBITDA; DuPont